AI Adoption in Southern African Open and Distance e-Learning: A Systematic Review - Tirivashe Mafuhure; Mampilo Phahlane; Charles Mbohwa (Journal of Information System and Informatics, 2026)
The integration of Artificial Intelligence (AI) into Open and Distance e-Learning (ODeL) systems is now a very important aspect in higher and tertiary education worldwide and this also includes Southern Africa. This paper reviewed a total number of 79 peer reviewed studies and other relevant publications from the year 2019 to 2025, examining how AI was being employed to improve teaching, research, learning, and administration processes in ODeL institutions in the Southern Africa region. This research study explored how AI was used address challenges that are peculiar to the Southern African region by looking on aspects to do with high student to instructor ratio, resource constraints, lack of proper expertise, and limited digital infrastructure. Findings from the research study reveal that although AI can offer solutions such as Personalised learning, automation of administrative processes, enhanced learner engagement, and automated assessments, its implementation in most ODeL institutions is hindered by lack of proper infrastructure, lack of expertise, and policy gaps. The review highlighted the need for regional collaboration among Higher Education ODeL institutions, investment in ICT infrastructure, and comprehensive policy development for successful implementation of AI. Findings obtained can assist major stakeholders that include Higher education leaders, policymakers, researchers and students on the potential of AI to transform Open and Distance electronic Learning in Southern Africa.